2017
DOI: 10.1002/cpp.2151
|View full text |Cite
|
Sign up to set email alerts
|

Impaired emotion processing and a reduction in trust in patients with somatic symptom disorder

Abstract: There is accumulating evidence for deficits in the perception and regulation of one's own emotions, as well as the recognition of others' emotions in somatic symptom disorder (SSD). However, investigations of SSD focusing on specific aspects of emotion processing and how these might interact are missing. We included 35 patients with SSD and 35 healthy controls who completed questionnaires on the perception and regulation of their own emotions, as well as experimental investigations of emotion recognition and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 59 publications
(76 reference statements)
5
23
1
2
Order By: Relevance
“…Our unexpressed feelings find a way to express themselves in a way. One of the most concrete signs of this is somatic complaints [47]. Another finding in our study is consistent with studies in the literature related to alexithymia and somatic complaints.…”
Section: Discussionsupporting
confidence: 93%
“…Our unexpressed feelings find a way to express themselves in a way. One of the most concrete signs of this is somatic complaints [47]. Another finding in our study is consistent with studies in the literature related to alexithymia and somatic complaints.…”
Section: Discussionsupporting
confidence: 93%
“…Difficulties with identifying one's own feelings, known as alexithymia, are well studied within somatoform patients (Erkic et al, 2017). The lack of specific vulnerability factors in the form of schemas might also be due to shared aetiological factors of somatoform, anxiety, and depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Rief, Ihle, and Pilger (2003) described typical illness behaviour for patients with somatoform disorders, for example, a high number of medical consultations in order to verify a diagnosis, social withdrawal, and taking unnecessary medication. Furthermore, a number of studies have investigated emotional processing abilities in somatoform patients and found that alexithymia is higher in somatoform disorders than in healthy controls (Bankier, Aigner, & Bach, 2001;Erkic et al, 2017;Pedrosa Gil et al, 2009;Waller & Scheidt, 2004). Furthermore, a number of studies have investigated emotional processing abilities in somatoform patients and found that alexithymia is higher in somatoform disorders than in healthy controls (Bankier, Aigner, & Bach, 2001;Erkic et al, 2017;Pedrosa Gil et al, 2009;Waller & Scheidt, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Affect avoidance and difficulty in acknowledging and expressing negative affects are shared characteristics of patients with cluster C personality disorders (or traits of them) and those with somatic symptom disorder, both of which are important aspects observed in Doris. 27 In IS 1 In summary, this study concludes that ISs, which can be empirically observed using the PQS, make up the psychotherapeutic process. In this case, the best model identified was a composite of four factors, some of which were similar to those in other studies (interactions regarding the therapeutic alliance are quite common), whereas others were probably unique to the process here described.…”
Section: Assessment Of Treatment Outcomementioning
confidence: 61%